Art Integration: The Missing Piece of the Puzzle - Teotia, Anil Kumar (THE PRIMARY TEACHER, 2025)
Art contributes to learning in ways that go beyond learning basic reading, writing and arithmetic, also known as the 3Rs. In fact, art is a pedagogical tool for making learning fun and accessible to children. Through this study, the researcher tried to study the perception of Delhi government teachers regarding art integration into learning. It was found that teachers are well aware of the benefits of integrating art into their classrooms. However, the level of art integration in regular classrooms is extremely poor. Teachers are unable to leverage the potential of art integration as a pedagogical tool in classrooms. The reasons behind this poor level of usage are also investigated and shared. Some corrective measures in the form of recommendations are also shared at the end of the article.